2003
DOI: 10.1177/0013916503254746
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Zoo Visitor’s Experience by Public Animal Training and Oral Interpretation at an Otter Exhibit

Abstract: This study investigated the effects of performing animal-training sessions with Asian small-clawed otters ( Aonyx cinerea) while zoo visitors watched. The effects of having an interpreter present to describe the otters and their training on zoo visitors were also assessed. The data from 389 visitors to Zoo Atlanta’s otter exhibit were analyzed, and exhibit stay times and animal activity levels were recorded during four conditions (passive exhibit viewing, interpretation-only sessions, public animal- training s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 26 publications
4
73
0
1
Order By: Relevance
“…Anderson et al, 2003), no variation was found with this particular collection method. Additionally, both bears were inactive for many of the interviews, yet the majority of visitors still had very positive comments about the animals.…”
Section: Discussion Visitor Perceptionsmentioning
confidence: 65%
“…Anderson et al, 2003), no variation was found with this particular collection method. Additionally, both bears were inactive for many of the interviews, yet the majority of visitors still had very positive comments about the animals.…”
Section: Discussion Visitor Perceptionsmentioning
confidence: 65%
“…Consider a group of students who attend an otter training session during a zoo excursion. Animal training sessions may effectively capture people's attention and arouse an interest in the zoo visitor (U. S. Anderson, Kelling, Pressley-Keough, Bloomsmith, & Maple, 2003).…”
Section: Conceptualising Student Interestmentioning
confidence: 99%
“…One common way that zoos and aquariums use personal interpretation is through public animal training sessions. Live animals have been used successfully in education programs to create positive impacts in visitor knowledge gain and conservation attitudes [Sherwood et al, 1989;Yerke and Burns, 1991;Heinrich and Birney, 1992;Yerke and Burns, 1993;Swanagan, 2000;Povey and Rios, 2002;Anderson et al, 2003]. Animal training has been used in zoos and aquariums to educate visitors [Ramirez, 1999;Hiatt et al, 2003] as well as for enrichment [Mellen and Sevenich MacPhee, 2001;Sevenich MacPhee and Mellen, 2002] and husbandry purposes [Desmond and Laule, 1994;Grandin et al, 1995;Hellmuth, 1995;Bloomsmith et al, 1998].…”
Section: Current Status Of Using Animal Training In Public Programsmentioning
confidence: 99%